Enhancing ROSS Network Reliability Through Evolutionary Optimization Techniques - Mohsen Abboud, Sahab; Musleh salman, Abbas; Ali Shakir, Qasim; Hadi Hussain, Ahmed (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
This research aims to develop computational models to improve resource allocation and increase the reliability of a ROSS (Relay-based Opportunistic Spectrum Sharing) network. The focus is on using two intelligent algorithms, the genetic algorithm (GA) and the particle swarm algorithm (PSO), to achieve efficient optimization. A mathematical model is constructed that determines relay locations and spectrum sharing methods to reduce the probability of failure and increase reliability. The algorithms are based on evaluating an objective function that takes into account spectrum efficiency, network delay, and connection reliability. The results show that using GA and PSO leads to significant performance improvements compared to traditional methods. The impact of the number of relays and secondary users on allocation efficiency is also analyzed. Combining the two algorithms contributes to accelerating the achievement of near-optimal solutions. Finally, the proposed model provides a general framework that can be applied to various types of dynamic spectrum networks.